"FROM AUTOMATION TO AUGMENTATION: AI'S JOURNEY IN HR" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Enterprises form the cornerstone of a nation's economy, and history reveals three distinct waves of industrial transformation that have shaped the modern world over the past two centuries. The advent of mechanical machinery marked the beginning of Industry 1.0 in the 18th century, followed by the steam-powered Industry 2.0 in the 19th century. The 20th century ushered in Industry 3.0 with the proliferation of computers and the internet (PWC Report, 2017). Now, in the 21st century, Industry 4.0 has emerged, characterized by revolutionary technologies like the Internet of Things (IoT), big data analytics, artificial intelligence (AI), and high-speed data networks such as 4G and 5G.